E-bakery ordering system - Nor'ain, Ismail (2005)
This system is been develop in order to fulfill the "Project Sarjana Muda"requirement which is entitle E-Bakery Ordering System (E-BOS).This system is based on the case study from the Dislee Cake House (DCH),situated in Benteng,Kuantan. EBOS is a system which are able the DCH customers do the online cakes, cookies and breads ordering via the internet and also the administrator of the cake house able to manage all the products ordering and customers information in more effective which,the all the information will be keep into the database.After done some survey and interviews with the owner of the DCH,Mr Sim Yeow there is no any online application had been implemented in the cake house, furthermore,all the products and customers information are kept in file based system. As these problems are concerned, E-BOS had been designed to overcome those problems whereby, this system is basically is a web based application which are able the customers to do their bakeries ordering activities just via the internet and the DCH itself able to manage their activities detail such as customers ordering,products and customers information effectively and more manageable which means most of the activities that involve in this DCH had been computerized. Last but not least, with the help of E-BOS,the ordering processes can be done easily, more manageable customers and products information and also most of the manuals activities of ordering and sales management are computerized.